A POSSIBLE RELATIONSHIP BETWEEN SERUM HOMOCYSTEINE LEVEL AND IgA NEPHROPATHY IN CHILDREN - Cemile Pehlivanoğlu; Zeynep Nagehan Yürük Yıldırım; Alev Yılmaz; Asuman Gedikbaşı; Nurinisa Karagöz; Nurver Akıncı; Aysel Kıyak; Gül Özçelik; Mesude Yasemin Özlük; Işın Kılıçaslan; Ayşe Ayşim Özağarı; Bağdagül Yavaş Aksu; et al. (İstanbul Tıp Fakültesi Dergisi)
Objective: The evidences from experimental and epidemiological studies suggests that elevated serum homocysteine levels may lead to renal injury and may be a significant risk factor for the development of chronic kidney disease. The aim of this study was to investigate a possible relationship between serum homocysteine level and crescent formation in children with IgA nephropathy and Henoch-Schonlein purpura nephritis. Material and Methods: A total of 31 patients diagnosed as biopsy proven IgA nephropathy and Henoch-Schonlein purpura nephritis and idiopathic crescentic glomerulonephritis in three Pediatric Nephrology centers within the last five years and 25 healthy controls were enrolled in the study. Results: Homocysteine levels of patients were higher than the upper limit of normal value and also higher than the controls (p=0.0001). There was no significant difference between the patients with or without crescent formation regarding homocysteine levels (p>0.05). Presence or severity of proteinuria was not related to homocysteine levels (p>0.05). Conclusion: Serum homocysteine levels are elevated in patients with IgA nephropathy and Henoch-Schonlein purpura nephritis.Our results suggest that elevated serum homocysteine levels may be related to segmental glomerulosclerosis in these patient groups.